Surface structuring of β-TCP and transition to α-TCP induced by femtosecond laser processing - Aceti, D. M.; Filipov, E.; Sotelo, Lamborghini; Fontanot, T.; Christiansen, S.; Lasgorceix, M.; Leriche, A.; Buchvarov, I.; Daskalova, A. (Journal of Physics: Conference Series, 2023)
Tricalcium phosphate (Ca3(PO4)2, TCP), is one of the most studied and used as material for bioresorbable implants. The β phase has a slower dissolution dynamic and ensures mechanical support for a longer time in biological environment, while a faster release of ions characterize the α phase that trigger a stronger biological response. In this work a femtosecond laser system was used to process β-TCP pellets surface. The femtosecond laser processing results in surface morphology modification, by turning the flat mirror polished surface into a rough and opaque one. The morphological and phisycochemical characteristics of material surface were studied by means of SEM, AFM, Raman, XRD and contact angle measurement. The processed surface showed the formation of micro and nano roughness alongside, furthermore a partial phase transformation from β-TCP to α-TCP was detected. A significant improvement in surface wettability for three different liquids (i.e.water, ethylene glycol and diiodo-methane) is reported. This implies an increase in surface free energy as well. The combination of α and β phase, together with the increased roughness obtained by laser processing, could positively affect the cell adhesion and metabolic activity.
CRIS-Team Scopus Importer:2023-06-02